Changes in micronutrient supply to the surface Southern Ocean (Atlantic sector) across the glacial termination - Hendry, K; Rickaby, R; Allen, C (2011)
Major deepwater masses upwell and reach the surface in the Southern Ocean, forming an important conduit supplying nutrients and micronutrients to the surface and playing a key role in the regulation of global climate through ocean-atmosphere gas exchange. Here, we reconstruct changes in micronutrient distribution in this region in response to past changes in upwelling, oceanic mixing, and sea-ice seasonality. We present two downcore (Zn/Si)opal records from the Scotia Sea and Drake Passage region, which we interpret in the context of micronutrient distribution in the Atlantic sector of the Southern Ocean over the last glacial termination. Previous work shows that micronutrient availability in the surface waters in the South Atlantic appear to be controlled dominantly by upwelling and mixing of micronutrient rich deepwaters, which are additionally fuelled by the terrestrial sediment sources of the Scotia Arc and South Georgia. This is supported by our reconstructions, which show micronutrient availability to the west of the Scotia Arc and South Georgia are consistently lower than to the east over the last glacial termination due to downstream transport and mixing into surface waters of continentally derived material in the Antarctic Circumpolar Current. Micronutrient availability in this region was at a minimum from 20 to 25 ky BP, coinciding with maximum sea-ice coverage, and increased due to an expansion of the seasonal sea-ice zone and increased mixing of subsurface waters. Our findings are consistent with largely diminished upwelling of micronutrients during the maximum glacial extent, and reduced mixing due to the presence of persistent sea-ice. During the deglacial there was an increase in micronutrient availability, as well as other nutrients and inorganic carbon, within the Antarctic Circumpolar Current as a result of an increase in deep oceanic upwelling, mixing and strengthened zonal transport. Copyright © 2011 by the American Geophysical Union.